2015
DOI: 10.1016/j.archoralbio.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two multilocus sequence typing (MLST) schemes available for Streptococcus mutans

Abstract: Objective Two multilocus sequencing typing (MLST) schemes are currently available for Streptococcus mutans. The first, introduced by Nakano et al. in 2007, consists of 8 conserved housekeeping genes. The second, introduced in 2010 by Do et al., includes 6 housekeeping genes and 2 putative virulence genes. The purpose of the current study was to compare the two MLST schemes for use in validating repetitive extragenic palindromic polymerase chain reaction (rep-PCR) genotypes. Design Thirty-three S. mutans isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…For instance, 2,110 isolates are reported for G18 and all of these isolates are uniform in their rep-PCR gel images. In addition the same ST (166) has been found for all isolates tested for G18 with MLST in other studies (Momeni et al, 2015). However, due to the allowance for up to 2 minor band differences, other genotypes, such as G12, demonstrate subtle genetic drift as more isolates are evaluated.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, 2,110 isolates are reported for G18 and all of these isolates are uniform in their rep-PCR gel images. In addition the same ST (166) has been found for all isolates tested for G18 with MLST in other studies (Momeni et al, 2015). However, due to the allowance for up to 2 minor band differences, other genotypes, such as G12, demonstrate subtle genetic drift as more isolates are evaluated.…”
Section: Discussionsupporting
confidence: 70%
“… (range: 15–21 sites) but consistent with our previous study (range: 6–12 sites) (Table ). The number of variable nucleotide sites was highest in gltA in all three studies but lowest in gyrA in both Uniontown studies . In the present study, gyrA was found to have a dN/dS of >1, which indicates positive selection for this gene in the isolates evaluated in this study.…”
Section: Discussionsupporting
confidence: 46%
“…Forty isolates were classified into one of the 16 new STs found in this study. Sixty matched previously published STs (19 isolates matched STs from the PubMLST database for Japanese, Thai, or Finnish isolates, and the remaining 41 isolates matched STs previously reported from the Uniontown population) .…”
Section: Resultsmentioning
confidence: 99%
“…Genomes were filtered based on the following criteria via blastall 2.2.26: genomes with a contig number of Ն200 and a scaffold of Ͻ500 bp, genomes not containing all MLST core genes, and/or genomes having a single gene copy number of Ͻ75% (30). Both Nakano's and Do's MLST approaches demonstrate similar discrimination for S. mutans (46). However, only two candidate genomes were preserved after data filtering based on Do's MLST scheme.…”
Section: Methodsmentioning
confidence: 99%